Korespondensi Preferensi dan Karakteristik Tipe Wisatawan Grup pada Kawasan Agrowisata - Diah Ayu Kendran; Hanson Endra Kusuma; Annisa Safira Riska (http://arl.faperta.ipb.ac.id/, 2021)
Facility planning will be successful if every process always consider the user and activities aspects. This aspects also applies to the agrotourism area, where tourist preference and segmentation can be used to understand visitor desires. This research aims to identify preferences and characteristics of the tourist segmentation in the visited agrotourism areas. This research used a grounded theory approach with qualitative exploratory methods. Data was collected online in an open–ended and close–ended questionnaire which was analyzed in 3 steps; open coding, axial coding, and selective coding. Based on the analysis results, tourists’ preference for visiting agrotourism area were to enjoy natural environment and do various recreational activities. The study also found the tourist characteristics was dominated by visitors who come in groups with close relationship of family and friends. The characteristics of these tourists can be used as a basis of harmonisation for determining the criteria of facilities in agrotourism where the implemented design can give attention to the sustainability (lifecycle) of tourist attraction from natural and economic aspect.